Use of Planar Chiral Ferrocenylphosphine‐Gold(I) Complexes in the Asymmetric Cycloisomerization of 3‐Hydroxylated 1, 5‐Enynes. Issue 1 (30th November 2015) - Wu, Zhiyong; Retailleau, Pascal; Gandon, Vincent; Voituriez, Arnaud; Marinetti, Angela
Abstract: Chiral monodentate phosphines based on ortho ‐disubstituted ferrocene units have been prepared and used for the synthesis of gold(I) complexes. These complexes are highly active catalysts for the cycloisomerization of 3‐hydroxy‐1, 5‐enynes into bicyclo[3.1.0]hexanones. Their high catalytic activity is ascribed to their structural analogy to the biaryl‐based Buchwald phosphines. This paper discloses the first enantioselective variant of these reactions based on gold catalysis ( ee 's up to 80 %). Abstract : Chiral monodentate phosphines have been prepared and used for the synthesis of gold(I) complexes. These complexes proved to be highly active catalysts for the first enantioselective gold‐catalysed cycloisomerization reactions of 3‐hydroxy‐1, 5‐enynes ( ee 's up to 80 %).